Analysis of Settlement Planning in the Lantawe Coastal Area, Napano Kusambi District, West Muna Regency - Brata, Joko Tri Brata; Heber; Toparakkasi , Fadhlih; Ruksanan (International Journal of Management and Education in Human Development, 2023)
Settlements in the coastal area are one of the unique types of areas that require a special approach in understanding their characteristics, thus this research aims to describe the strengthening of the characteristics of settlements in Lantawe and analyze the concept of planning for the development of settlement areas according to the typology and pattern of coastal settlements. The method used is a qualitative method by explaining the target performance of the area development plan in relation to benefits, by collecting as many in-depth facts as possible. This approach is used by the author because the subject of the research study is in the form of a typology description and a program for handling coastal settlements. The results of the study illustrate that there are 3 building typologies, namely; (1) Typology of Water Buildings, (2), Typology of Stage Buildings and (3) Typology of Land Buildings. The Direction of Residential Area Development is in the form of a program for handling slum areas into areas with unique characteristics as scenario 1, and Scenario 2 describes the planning and design of residential areas for the Affirmation of Regional Residential Identity, by carrying out; (1) identification of healthier residential areas and; and (2) reinforce regional identity.